Analysis of the Return of Evidence 220 to 258 in Decision Number 1240/Pid.sus/2022/PN.Tng With the Defendant Indra Kusuma or Indra Kenz (Perspective of the Principles of Justice, Benefit, and Al-Maslahah) - Adiyanto, Rahmad (Jurnal Hukum Ekonomi Syariah, 2023)
On August 14, 2022 the judge at the Tangerang district court stated that the defendant Indra Kusuma or Indra Kenz had spread false news which resulted in consumer losses in electronic transactions and money laundering, sentenced the defendant Indra Kenz to 10 years imprisonment and a fine of 10 billion, provided that if the sentence is not paid, it will be replaced with confinement for 10 years 2 months, and so on. Interestingly, in this decision the judge disagreed with the public prosecutor regarding the return of evidence number 220-254 to the victim-witness through the United Indonesian Traders Association because the goods were the result of a crime. Therefore the purpose of this study is to analyze aspectsal-'is (justice) andal-maslahah(benefits) viewed from the side of the victim and the accused. This research is a normative research with a normative juridical approach. This research uses secondary legal materials in the form of decisions 1240/Pid.sus/2022/PN.Tng, related laws, legal theories, theoriesal-'is, and theoryproblem. The research results show The judge's decision regarding the refusal to return evidence number 220-258 violates the principles of certainty, expediency and benefit in Islamic law. The researcher's solution is that the judge should select which evidence belongs to the victim and should return it to the victim.